Ruhiyah Pendidik Kunci Sukses Pendidikan - Ainal Mardhiah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2016)
Current conditions among students, rampant HIV, usage of marijuana, drug promiscuity very rampant everywhere, but the government continues to give more attention, including funds to be increased allocation for education. Changes in curriculum continues to do, until the character curriculum initiated on the date July 15, 2013, but did not affect much to anticipate the problem of moral and character of today's teenagers are increasingly widespread. All the components for a successful education is already available as a competent educators, students, curriculum, methods, media, infrastructure, and evaluation. For components that competent educators already holds a Bachelor's degree, Master's and even Doctorate degree. But the reality of what happened does not affect much to the improvement of morals, moral decadence still happens everywhere even among intellectuals, academics and government officials who should be an example for everyone. According to the authors, educators as an important component in addition to competent scholarly must also have personal competence especially must have high ruhiyah in order to move the students carry out all the material received. Making intelligent protégé intellectual, emotional and psychomotor more particularly intelligent character so protégé faithful, devoted, pious and noble deeds. This will make students avoid behaviors reprehensible and moral decadence rampant.